2017
DOI: 10.1371/journal.pmed.1002336
|View full text |Cite
|
Sign up to set email alerts
|

Timing of femoral shaft fracture fixation following major trauma: A retrospective cohort study of United States trauma centers

Abstract: BackgroundFemoral shaft fractures are common in major trauma. Early definitive fixation, within 24 hours, is feasible in most patients and is associated with improved outcomes. Nonetheless, variability might exist between trauma centers in timeliness of fixation. Such variability could impact outcomes and would therefore represent a target for quality improvement. We evaluated variability in delayed fixation (≥24 hours) between trauma centers participating in the American College of Surgeons (ACS) Trauma Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…An advantage of these Canadian data compared with data from the United States is the ability to capture exact wait times in hours (versus days) and the time elapsed in transfer between hospitals. 48,58 Other potential applications of these data include more accurately identifying afterhours surgery, 19 durations of surgery 59 and overlapping surgical procedures. …”
mentioning
confidence: 99%
“…An advantage of these Canadian data compared with data from the United States is the ability to capture exact wait times in hours (versus days) and the time elapsed in transfer between hospitals. 48,58 Other potential applications of these data include more accurately identifying afterhours surgery, 19 durations of surgery 59 and overlapping surgical procedures. …”
mentioning
confidence: 99%
“…Previous studies showed that delayed de nitive surgery for bone fracture (after 24 to 48 h) led to pulmonary complications such as pneumonia and acute respiratory distress syndrome because post-traumatic and post-surgical in ammation act as "two hit model" 22,37−39 . However, few studies have showed an association between timing of de nitive surgery and post-traumatic PE because it is a relatively infrequent complication 40 . A subgroup analysis in this study showed that bone xation during 24-120 h after injury was associated with a higher risk for PE.…”
Section: Resultsmentioning
confidence: 99%
“…However, debate persists regarding thromboembolic risk and compartment syndrome 25,26 . Concerning surgical timing, controversies have arisen with the birth of DCO, as opposed to the philosophy of early total care (ETC), relying on the immediate treatment of fractures 27 . ETC is not recommended in cases of polytrauma in a hemodynamically unstable patient and high blood levels of lactates.…”
Section: Discussionmentioning
confidence: 99%